In situ electrochemical generated metal hydroxides as coagulants for optimization of sulfamethoxazole removal - Omid Paknia; Mohammad Hassan Moshafi; Faeze Ashkar; Maryam Dolatabadi; Saeid Ahmadzadeh (Scientific Reports)
Abstract In this study, the antibiotic sulfamethoxazole (SMX) removal was investigated and optimized using the electrocoagulation process (ECP). The effective parameters including initial SMX concentration, current density, solution pH, reaction time, type and concentration of supporting electrolytes, and types of electrodes (Fe/Fe, Al/Al, Cu/Cu, and Zn/Zn), on the treatment process were investigated. Response surface methodology (RSM) applied for designing the study based on central composite design (CCD). The maximum treatment efficiency and energy consumption of 99.9% and 0.743 kWh m−3, respectively, was found in the optimum process condition including initial SMX concentration of 20 mg L−1, current density of 15.0 mA cm−2, solution pH of 9.0, reaction time of 17.0 min, 20 mM of NaCl as supporting electrolyte using Fe/Fe electrode. The statistical data including p-value of < 0.0001, F-value of 311.2, high determination coefficient (R2) of 0.9878, adjusted R2 of 0.9847, and predicted R2 of 0.9753 were revealed satisfactory correlation between the predicted values and experimental findings for the developed model. The ECP involves a combination of multiple mechanisms such as coagulation, flocculation, flotation, sedimentation, and adsorption that act synergistically to remove contaminants by applying electrical current.